The impact of host plant species on instar duration and body weight of nymphal Lycorma delicatula - Kreitman, Devin; Keena, Melody A.; Nielsen, Anne L.; Hamilton, George (Frontiers in Insect Science, 2023)
The spotted lanternfly Lycorma delicatula (White) (Hemiptera: Fulgoridae) is an invasive species of planthopper that was introduced to North America and a threat to multiple industries. Nymphs and egg masses were collected to assess each instar’s rate of development at a constant 25°C on the following hosts: Ailanthus altissima (Miller) (Sapindales: Simaroubaceae), Vitis labrusca (L.) (Vitales: Vitaceae) Salix babylonica (L.) (Malpighiales: Salicaceae), Acer rubrum (L.) (Sapindales: Sapindaceae), Celastrus orbiculata (Thunberg) (Celastrales: Celastraceae), Ocimum basilicum (L.) (Lamiales: Lamiaceae), and Rosa multiflora (Thunberg) (Rosales: Rosaceae). Host plant was found to have significant effect on development time for nymphs in the first through third instar as well as on nymphal survival. Nymphs failed to develop through the second instar on O. basilicum and the third and fourth instar on A. rubrum. Host plant also had a significant effect on the mean weight of nymphs in the first, second, and fourth instar, but not the third instar and on adult hind tibia length and forewing width. This variability in L. delicatula development time by host plant can potentially impact phenology models and should be updated to reflect these new insights. Rearing practices should also be refined to account for host plant influences on their physiology as well.